1993
DOI: 10.1021/j100125a009
|View full text |Cite
|
Sign up to set email alerts
|

Large intramolecular energy flow in vibrational overtone spectra of cyclohexene-3,3,6,6-d4

Abstract: The vibrational structure of CH stretching states in gas-phase cyclohexene-3,3,6,6-d4 was studied using FTIR spectroscopy in the range 1200-1 1500 cm-1 and intracavity dye laser photoacoustic spectrometry in the range 12900-16000 cm-l. The structure was modeled using an effective vibrational Hamiltonian which describes the Fermi resonance couplings of the C H stretching states with suitable low-frequency vibrations. Some conclusions are made on the possible ways of intramolecular vibrational redistribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…35, but agrees with an ab initio study by Polavarapu et al, 43 by which it was found that the calculated CH-bond lengths are more dependent from the conformation than from the distance from the C=O; in passing, we observe that a discrepancy between the findings of infrared and NIR data was pointed out in Ref. 36, in commenting the results for cyclohexene and cyclopentene. The same can be said for cyclohexanone, where the experimental accuracy in the determination of and is not as high as for cyclopentanone, since the assignment and deconvolution of individual bands is poorer: indeed, the values for the parameters at the ␣-positions reported in Table 1 are determined from weak features and shoulders of perhydrocyclohexanone spectra.…”
Section: Determination Of the Spectroscopic Parameters For (R)-limonesupporting
confidence: 92%
See 2 more Smart Citations
“…35, but agrees with an ab initio study by Polavarapu et al, 43 by which it was found that the calculated CH-bond lengths are more dependent from the conformation than from the distance from the C=O; in passing, we observe that a discrepancy between the findings of infrared and NIR data was pointed out in Ref. 36, in commenting the results for cyclohexene and cyclopentene. The same can be said for cyclohexanone, where the experimental accuracy in the determination of and is not as high as for cyclopentanone, since the assignment and deconvolution of individual bands is poorer: indeed, the values for the parameters at the ␣-positions reported in Table 1 are determined from weak features and shoulders of perhydrocyclohexanone spectra.…”
Section: Determination Of the Spectroscopic Parameters For (R)-limonesupporting
confidence: 92%
“…Since the same signals are present for cyclopentanone-2,2,5,5-d 4 and cyclohexanone-2,2,6,6-d 4 , with the same frequencies and with an intensity decrease equal to the number of deuterium atoms replacing the hydrogens, 12,13 we assign the two signals to axial and equatorial CH-bond stretchings in either ␣, ␤, and ␥ (for cyclohexanone) positions. The equatorial CH-bond stretchings have higher frequencies and intrinsic intensities, as has been observed in cyclohexene, 36 and as has been recognized and rationalized to some extent in a variety of ring molecules, comprising cyclohexane, 41 dioxane, tetrahydropyrane, and piperidine. 42 The previous overtone regions ⌬v = 2 and ⌬v = 3 (Figs.…”
Section: Determination Of the Spectroscopic Parameters For (R)-limonementioning
confidence: 70%
See 1 more Smart Citation
“…There are two kinds of off-diagonal couplings: the Fermi resonance couplings which are deduced from the first-order Hamiltonian 25 and the interbond coupling between the CH and CD stretchings.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…When the movement is slow enougth as in cyclohexene, there is no competition between the two phenomena, and the vibrational energy dynamics is essentially governed by the strong Fermi resonance couplings. 25 For more rapid motions, the two couplings have to be treated together. 27 For that purpose, the adiabatic approximation has proved to be a powerful tool to decouple the fast vibration from the slow large-amplitude motion in the first excited CH stretching state 28 as well as in higher overtones.…”
Section: Introductionmentioning
confidence: 99%